The impact of cryopreservation in signature markers and immunomodulatory profile of tendon and ligament derived cells - Gonçalves, A I (2022)
Tendon and ligament (T/L) engineering strategies towards clinical practice have been challenged by a paucity of understanding in the identification and still poorly described characterization of cellular niches. Prospecting how resident cell populations behave in vitro, and how cryopreservation may influence T/Â L-promoting factors, can provide insights intoÂ T/Â L-cellular profiles for novel regenerative solutions. Therefore, we studiedÂ human T/Â L-derived cells isolated from patellar tendons and cruciate ligaments as suitable cellular models to anticipate tendon and ligament niches responses for advanced strategies with predictive tenogenic and ligamentogenic value. Our results show that the crude populations isolated from tendon and ligament tissues hold a stem cell subset and share a similar behavior in terms of tenogenic/ligamentogenic commitment. Both T/Â L-derived cells successfully undergo cryopreservation/thawing maintaining the tenogenic/ligamentogenic profiles. The major differences between cryopreserved and fresh populations were observed at the gene expression ofÂ MKX, SCX, andÂ TNMDÂ as well as at the protein levels of collagen type I and III, in which cells from tendon origin (hTDCs) evidence increased values in comparison to the ones from ligament (hLDCs,Â pâ <â 0.05). In addition, low-temperature storage was shown to potentiate an immunomodulatory profile of cells, especially in hTDCs leading to an increase in the gene expression of the anti-inflammatory factorsÂ IL-4Â andÂ IL-10Â (pâ <â 0.05), as well as in the protein secretion of IL-10 (pâ <â 0.01) and IL-4 (pâ <â 0.001). Overall, the outcomes highlight the relevance of the cryopreserved T/Â L-derived cells and their promising immunomodulatory cues as in vitro models for investigating cell-mediated mechanisms driving tissue healing and regeneration.